Civil Liability of Police Officers in Ukraine and Germany: Legal Aspects and Problematic Issues - Чанишева, Галія Інсафівна; Чанишева, Г. І.; Чанишева, Галия Инсафовна; Chanysheva, Haliia I.; Chanysheva, Galiya; Chanysheva, Galiya I.; Юнін, Олександр Сергійович; Юнін, О. С.; Юнин, Александр Сергеевич; Yunin, Oleksandr S.; Міловська, Надія Василівна; Міловська, Н. В.; et al. (Jordan Whitney Enterprises, Inc., 2019)
Description: The article is to investigation of the peculiarities of civil liability of police officers in Ukraine and Germany. Methodology. The study used general scientific and special methods. Thus, the analysis and synthesis method as well as the logical method were used to develop a holistic view on the institution of civil liability of police in Ukraine and in Germany. The dialectical method made it possible to consider the state of scientific researches concerning this issue. The comparative legal method was used when analyzing German legislation on the issue under consideration. The logical-semantic method was used to establish the meaning of the term of “civil liability of police officers”. With the help of the normative-dogmatic method, the content of the normative-legal acts of domestic legislation governing the issue under consideration was analyzed. The use of the legal modeling method made it possible to develop proposals for the optimization of the current civil legislation of Ukraine concerning civil liability of police officers. The materials studied are the legislation of Ukraine and Germany as well as the scientific works of Ukrainian and foreign scientists on this subject. The results of the study made it possible to study the peculiarities of the civil liability of police officers in Ukraine and Germany, to examine the legislation of the countries under study that regulates this issue, to analyze the relevant provisions of the legal acts and to conclude that they need to be amended. Practical implications. According to the results of the research, proposals have been made to amend the Civil Code of Ukraine and the special law that regulates the issue of civil liability of police officers in Ukraine. Value/originality. On the basis of the study the advantages and disadvantages of legal framework, which regulates the issue of civil liability of police officers in Ukraine and Germany, were determined.

Опис: Стаття присвячена дослідженню особливостей цивільно-правової відповідальності поліцейських в Україні та Німеччині. Методологія. У дослідженні використовувалися загальнонаукові та спеціальні методи. Таким чином, метод аналізу та синтезу, а також логічний метод були використані для вироблення цілісного уявлення про інститут цивільно-правової відповідальності поліції в Україні та Німеччині. Діалектичний метод дозволив розглянути стан наукових досліджень з цього питання. Порівняльно-правовий метод був використаний при аналізі німецького законодавства з розглядуваного питання. Логіко-семантичним методом встановлено значення терміну «цивільна відповідальність поліцейських». За допомогою нормативно-догматичного методу проаналізовано зміст нормативно-правових актів вітчизняного законодавства, що регулюють розглянуте питання. Використання методу правового моделювання дало змогу розробити пропозиції щодо оптимізації чинного цивільного законодавства України щодо цивільно-правової відповідальності поліцейських. Дослідженими матеріалами є законодавство України та Німеччини, а також наукові праці українських та зарубіжних вчених з даної тематики. Результати дослідження дали змогу вивчити особливості цивільно-правової відповідальності поліцейських в Україні та Німеччині, вивчити законодавство досліджуваних країн, що регулює це питання, проаналізувати відповідні положення нормативно-правових актів та зробити висновок, що до них потрібно внести зміни. Практичні наслідки. За результатами дослідження внесено пропозиції щодо внесення змін до Цивільного кодексу України та спеціального закону, що регулює питання цивільно-правової відповідальності поліцейських в Україні. Цінність/оригінальність. На основі проведеного дослідження визначено переваги та недоліки законодавчої бази, яка регулює питання цивільно-правової відповідальності поліцейських в Україні та Німеччині.
Chanysheva G. I. Civil Liability of Police Officers in Ukraine and Germany: Legal Aspects and Problematic Issues / G. I. Chanysheva, O. S. Yunin, N. V. Milovska, R. V. Pozhodzhuk, V. V. Mazur // Journal of Legal, Ethical and Regulatory Issues, Vol. 22. - № 4. - Jordan Whitney Enterprises, Inc., 2019. – 9 p.
Keywords: civil liability; damage; non-pecuniary damage; police officers; Ukraine; Germany; positive experience; цивільна відповідальність; збиток; моральна шкода; поліцейські; Україна; Німеччина; позитивний досвід; Research Subject Categories::LAW/JURISPRUDENCE